Method for recovering high-selectivity decommissioned lithium battery layered oxide positive electrode fine powder
By using an aqueous treatment solution consisting of oxalic acid dihydrate, a reducing agent, and a coordination-type in-situ acid-releasing agent, lithium and transition metals can be dissolved and separated from the decommissioned lithium-ion battery layered oxide cathode under mild conditions. This solves the problems of severe equipment corrosion and high cost in existing technologies, and achieves highly selective and low-cost separation of lithium and transition metals.
Patent Information
- Application Number
- CN202510793206.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-10-24
AI Technical Summary
Existing wet recycling methods for layered oxide cathode materials in lithium-ion batteries suffer from problems such as severe equipment corrosion, high costs, difficulty in separating lithium and transition metals, and expensive extractants, making it difficult to rapidly and selectively recover lithium and transition metals under mild conditions.
An aqueous treatment solution consisting of oxalic acid dihydrate, a reducing agent, and a coordination-type in-situ acid-releasing agent is used to dissolve and separate lithium and transition metals from the decommissioned lithium-ion battery layered oxide cathode under mild conditions. The one-pot method achieves highly selective separation of lithium ions and transition metals, and lithium ions are recovered by sodium carbonate precipitation.
It enables rapid and highly selective separation of lithium and transition metals under mild conditions, simplifies process steps, reduces equipment corrosion and processing costs, and improves recovery rate and purity.
Smart Images

Figure CN120834313A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of retired lithium-ion battery recycling, and particularly relates to a mild and high-selectivity recovery method for retired lithium battery layered oxide positive electrode fine powder. BACKGROUND
[0002] With the wide application of lithium batteries in the fields of consumer electronics and vehicles, the recycling of waste lithium batteries has become a focus in the fields of resource recycling and environmental pollution. Layered oxide positive electrode materials widely used in lithium-ion batteries, such as lithium cobaltate (LiCoO2), nickel-cobalt-manganese ternary material (NCM), nickel-cobalt-aluminum ternary material (NCA), etc., contain a large amount of valuable metal elements (such as lithium, cobalt, nickel, manganese, etc.), and the recycling of these metals has important economic and environmental values.
[0003] Among various recovery processes, wet recovery has become a research hotspot in the field of waste lithium battery recycling due to its outstanding advantages such as mild operating conditions, high metal recovery rate, low impurities in products, and low energy consumption. The process route mainly includes two key steps of sample dissolution and ion recovery, that is, first, the collected waste layered oxide positive electrode material is completely dissolved with acid and reducing agent, and then the ions in the solution are separated and recovered by precipitation or extraction. It should be noted that the use of inorganic strong acid and reducing agent for sample dissolution, although the treatment efficiency is high, but it is easy to cause equipment corrosion, while the use of organic weak acid treatment liquid can reduce acid corrosion, but the acid consumption is large, the reaction temperature is high, and the time is generally longer. For ion recovery, the precipitation method is convenient to operate, but a large amount of alkali liquor needs to be added to adjust the mixed ion solution obtained in the previous step to neutral or alkaline, which has high cost, and the method is difficult to completely separate lithium and transition metal ions, resulting in that the purity of the product (precipitate) is often not ideal. Although the extraction method has good selectivity, the extractant is expensive, for example, the price of manganese and cobalt extractant D2EHPA (di-(2-ethylhexyl) phosphate) is very high.
[0004] In view of the above bottleneck problems, it is urgent to develop a new type of efficient wet recovery method, which can quickly leach metal ions under mild conditions and completely separate lithium and transition metals, while reducing the treatment cost. SUMMARY
[0005] The purpose of the present application is to provide a mild and high-selectivity recovery method for retired lithium battery layered oxide positive electrode fine powder to solve the technical defects existing in the prior art.
[0006] A high-selectivity recovery method for retired lithium battery layered oxide positive electrode fine powder, comprising the following steps: S1, obtaining a fine powder material by pretreating a retired lithium battery layered oxide positive electrode sheet; S2, oxalic acid dihydrate, reducing agent and coordination in-situ acid releasing agent are dissolved in deionized water in proportion to obtain an aqueous treatment solution; S3, the fine powder material is added to the aqueous treatment solution, heated and stirred until the reaction is completed, and then allowed to stand to obtain a solid mixture; S4, after solid-liquid separation of the solid mixture, sodium carbonate is added to the liquid substance to prepare a solid lithium carbonate material, and the solid substance is collected after washing and drying to obtain the recovered positive electrode material.
[0007] Further, the pretreatment in S1 is: the retired lithium battery layered oxide positive electrode sheet is sequentially subjected to high temperature calcination, impurity removal and grinding treatment to obtain a fine powder material, and the content of the layered oxide in the fine powder material is more than 99%.
[0008] Further, the layered oxide is one or a combination of lithium cobalt oxide (LiCoO2), nickel cobalt manganese ternary oxide (LiNi x Co y Mn 1-x- y O2) or nickel cobalt aluminum ternary oxide (LiNi x Co y Al 1-x-y O2).
[0009] Further, in S2, the reducing agent is one or a combination of sodium sulfite, sodium bisulfite, potassium sulfite, potassium bisulfite, hydrogen peroxide; The coordination in-situ acid releasing agent is one or a combination of malic acid, gluconic acid, ascorbic acid, tartaric acid, citric acid, succinic acid, tannic acid, N-acetylglycine.
[0010] Further, in S2, in the aqueous treatment solution, the concentration of oxalic acid dihydrate, reducing agent and coordination in-situ acid releasing agent is 0.1-1.0 mol / L; and the molar ratio of oxalic acid dihydrate: reducing agent: coordination in-situ acid releasing agent is 1.0: 0.8-1.2: 0.8-1.2.
[0011] Further, in S3, the solid-liquid ratio of the fine powder material to the treatment solution is 9.65-96.5 g / L; and the molar ratio of the fine powder material: oxalic acid dihydrate is 0.9-1.1:1.
[0012] Further, in S3, the heating temperature is 50-100 ℃, the reaction time is 10 min-2 h, and the standing time is 1-4 h.
[0013] Further, in S4, the lithium ion concentration in the liquid substance is 2.0-8.0 g / L, and the pH value ranges from 6.5 to 7.5.
[0014] The application of the above recovery method to the recovery of retired sodium battery layered oxide positive electrode fine powder.
[0015] A sodium ion battery, wherein the positive electrode material of the sodium ion battery is the positive electrode material obtained by the above recovery method.
[0016] The mild and high-selectivity recovery method for the retired lithium battery layered oxide positive electrode fine powder has the following beneficial effects compared with the prior art: (1) Mild reaction conditions: This method does not use strong corrosive inorganic acid, and part of the hydrogen ions required for dissolution and conversion are gradually released by the coordination type in-situ acid releasing agent, so it will not cause significant corrosion to the equipment.
[0017] (2) Fast reaction rate: At the same temperature, the reaction rate can be comparable to the effect of using strong acid treatment, low temperature and short time. The reactions in the series conversion process are organically coupled and mutually promoted, so the leaching and conversion processes can be completed in a short time under mild conditions.
[0018] (3) Simplify process steps: The fine powder is converted into transition metal dihydrate oxalate precipitate and lithium ion-rich near-neutral solution through one-pot series conversion, and the transition metal ions are all precipitated as dihydrate oxalate, while the lithium ions remain in the supernatant. That is, high-selectivity separation of lithium ions and transition metal ions is completed in one step, and subsequent pH adjustment is not required, and lithium ions can be recovered by sodium carbonate precipitation.
[0019] (4) High reagent utilization rate: only the almost equivalent amount of dihydrate oxalate, reducing agent and coordination type in-situ acid releasing agent to the treated fine powder is required to complete the reaction, without the need for excess addition, thereby greatly saving the treatment cost. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 is a reaction process pH value-time curve diagram of the present application examples 1-3 and comparative example 1; Figure 2 is the Li + leaching rate-time curve of the supernatant of the present application examples 1-3 and comparative example 1; Figure 3 is the XRD test diagram of the recovered dihydrate oxalate obtained by NCM fine powder, LCO fine powder, examples 1-3 and comparative example 1. DETAILED DESCRIPTION The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.
[0021] The present application provides a high-selectivity recovery method of lithium battery layered oxide positive electrode fine powder, comprising the following steps: S1, the retired lithium battery layered oxide positive electrode sheet is pretreated to obtain a fine powder material; specifically, the pretreatment process of the retired lithium battery layered oxide positive electrode sheet is to sequentially pass through high-temperature calcination, impurity removal and grinding treatment to obtain a fine powder material, and the content of the layered oxide in the fine powder material is more than 99%; The layered oxide is one or more of lithium cobalt oxide (LiCoO2), nickel-cobalt-manganese ternary oxide (LiNi x Co y Mn 1-x-y O2) or nickel-cobalt-aluminum ternary oxide (LiNi x Co y Al 1-x-y O2).
[0022] S2, oxalic acid dihydrate, a reducing agent and a coordination type in-situ acid releasing agent are dissolved in deionized water in proportion to obtain an aqueous treatment solution; in order to ensure complete dissolution of the oxalic acid dihydrate, the reducing agent and the coordination type in-situ acid releasing agent, heating treatment can be used to promote the dissolution efficiency during the dissolution process.
[0023] The reducing agent is one or a combination of several of sodium sulfite, sodium bisulfite, potassium sulfite, potassium bisulfite and hydrogen peroxide; The coordination type in-situ acid releasing agent is one or a combination of several of malic acid, gluconic acid, ascorbic acid, tartaric acid, citric acid, succinic acid and tannic acid; The concentration of the oxalic acid dihydrate, the reducing agent and the coordination type in-situ acid releasing agent in the aqueous treatment solution is 0.1-1.0 mol / L; The molar ratio of the oxalic acid dihydrate, the reducing agent and the coordination type in-situ acid releasing agent is 1.0:0.8-1.2:0.8-1.2.
[0024] S3, the fine powder material is added to the aqueous treatment solution, heated and stirred until the reaction is completed, and then the solid mixture is obtained by standing; The solid-liquid ratio of the fine powder material to the aqueous treatment solution is 9.65-96.5 g / L:1. And the fine powder material: oxalic acid dihydrate = 0.9~1.1:1 in terms of the amount of substance.
[0025] The temperature condition of the heating is 50~100 ℃, the reaction time is 10 min~2 h, and the standing time is 1~4 h.
[0026] S4. After the solid-liquid separation of the solid mixture, the supernatant is filtered through a filter membrane with a pore size of 0.22 μm to obtain a lithium-rich solution, i.e., a liquid substance, and the liquid substance is precipitated using sodium carbonate to obtain solid lithium carbonate; the solid substance is a transition metal oxalate dihydrate, which is washed with deionized water and dried to be collected.
[0027] Specifically, in this step, the lithium ion concentration in the liquid substance is 2.0~8.0 g / L, and the pH value is in the range of 6.5~7.5, and the solid substance is a transition metal oxalate dihydrate corresponding to the transition metal contained in the fine powder material.
[0028] The recycling method of the present application not only overcomes the problems of large consumption of acid and base, serious acid corrosion, high cost and the like existing in the ion recovery of the existing sample dissolution, but also has the advantages of simple operation, good selectivity, high recovery rate, easy scaling up and the like, and is expected to promote the green and sustainable development of the lithium battery recycling field.
[0029] The second protection of the present application is the application of the recycling method in recycling the fine powder of the retired sodium battery layered oxide positive electrode.
[0030] The third protection of the present application is a sodium ion battery, and the positive electrode material of the sodium ion battery is the positive electrode material obtained by the recycling method.
[0031] Example 1 A high-selectivity recycling method of retired lithium battery layered oxide positive electrode fine powder, comprising the following steps: S1. Take the retired NCM ternary lithium battery layered oxide positive electrode powder, remove impurities by calcining at 650 ℃ for 3 h, and then grind into powder with a mortar to obtain NCM fine powder; S2. Weigh 630.4 mg of oxalic acid dihydrate, 630.2 mg of sodium sulfite and 880.6 mg of ascorbic acid, dissolve them in 10 mL of deionized water, heat to 80 ℃, and stir to obtain a treatment solution; S3. Weigh 482.5 mg of NCM fine powder obtained in S1 and add it to the treatment solution prepared in S2, keep the heating temperature at 80 ℃, stir for 20 min, and observe that the black fine powder is completely converted into gray-white transition metal oxalate dihydrate, and the gray-white solid is completely precipitated to the bottom after standing at room temperature for 40 min; S4. Solid-liquid separation was performed using a high-speed centrifuge at a speed of 10,000 r / min for 10 min; the supernatant was poured out, and a lithium-rich solution was obtained by passing through a membrane with a pore size of 0.22 μm; the lithium-rich solution was heated to 95 ℃, and an excess of 20% of sodium carbonate solid particles was added thereto; stirring was performed for 60 min, and lithium carbonate solid was obtained by hot filtration; the bottom precipitate after centrifugation was directly filtered, washed with 50 mL of deionized water, and collected after drying in a 60 ℃ oven to obtain a Ni, Co, and Mn-containing hydrated dihydrate oxalate cathode fine powder material.
[0032] Example 2 A high-selectivity recovery method of a retired lithium battery layered oxide cathode fine powder, comprising the following steps: S1. A retired lithium cobalt oxide (LCO) battery cathode powder was taken, impurities were removed by calcination at 700 ℃ for 2 h, and then the powder was ground into a powder using a mortar to obtain an LCO fine powder. S2. 1040.2 mg of dihydrate oxalic acid, 1187.0 mg of potassium sulfite, and 1069.5 mg of succinic acid were weighed and dissolved in 10 mL of deionized water, heated to 50 ℃, and stirred to obtain a treatment solution. S3. 734.1 mg of the LCO fine powder obtained in S1 was added to the treatment solution prepared in S2, the temperature was maintained at 50 ℃, and stirring was performed for 2 h; it was observed that the black fine powder was completely converted into a brown-red hydrated dihydrate cobalt oxalate precipitate; the brown-red solid was completely precipitated to the bottom after standing at room temperature for 2 h. S4. The supernatant was sucked out using a syringe, passed through a membrane with a pore size of 0.22 μm to obtain a lithium-rich solution, heated to 95 ℃, and an excess of 20% of sodium carbonate solid particles was added thereto; stirring was performed for 60 min, and lithium carbonate was obtained by hot filtration; the bottom precipitate was directly filtered, washed with 50 mL of deionized water, and collected after drying in a 60 ℃ oven to obtain dihydrate cobalt oxalate solid.
[0033] Example 3 A high-selectivity recovery method of a retired lithium battery layered oxide cathode fine powder, comprising the following steps: S1. A retired NCM ternary lithium battery cathode sheet was taken, impurities were removed by calcination at 550 ℃ for 4.5 h, and then the sheet was ground into a powder using a mortar to obtain an NCM fine powder.
[0034] S2. 315.2 mg of dihydrate oxalic acid and 432.3 mg of citric acid were weighed and dissolved in 9.71 mL of deionized water; 0.29 mL of 30% hydrogen peroxide solution was removed using a pipette and added thereto; and stirring was performed to obtain a treatment solution.
[0035] S3. Weigh 241.3 mg of NCM fine powder obtained in S1 into the treatment solution prepared in S2, heat to 70 ℃ under sealed conditions, and stir for 60 min. It can be observed that the black fine powder is completely converted into grayish white transition metal dihydrate oxalate. Stand for 30 min until the grayish white solid completely precipitates to the bottom; S4. The solid-liquid mixture obtained in S3 is subjected to suction filtration, and the filter membrane has a pore size of 0.22 μm. The lithium-rich solution is collected, heated to 95 ℃, and then 20% excess sodium carbonate solid particles are added thereto, stirred for 60 min, and hot filtered to obtain lithium carbonate solid. The precipitate on the filter membrane is collected, washed again by suction filtration with 50 mL of deionized water, dried in a 60 ℃ oven, and then collected to obtain transition metal dihydrate oxalate.
[0036] Comparative Example 1 A recovery method for leaching retired lithium battery layered oxide positive electrode fine powder using strong acid and reducing agent, comprising the following steps: S1. Take the retired NCM ternary lithium battery positive electrode material, calcine at 600 ℃ for 3.5 h to remove impurities, grind into powder with a mortar, and obtain NCM fine powder; S2. Prepare a mixed treatment solution of 2.0 M sulfuric acid and 6% hydrogen peroxide; S3. Weigh 482.5 mg of NCM fine powder obtained in S1 into the treatment solution prepared in S2, heat to 80 ℃, stir until the fine powder is completely dissolved, and the required time is 120 min. Collect the leaching solution; S4. Adjust the leaching solution obtained in S3 to a pH value of 7.0 using 1.0 M sodium hydroxide, add 804.0 mg of sodium oxalate dihydrate, stir for 60 min, and stand for 60 min until the transition metal dihydrate oxalate precipitates.
[0037] S5. Use a syringe to suck the supernatant, pass through a membrane with a pore size of 0.22 μm to obtain a lithium-rich solution, heat the lithium-rich solution to 95 ℃, then add excess 20% sodium carbonate solid particles thereto, stir for 60 min, and hot filter to obtain lithium carbonate solid. Filter the transition metal dihydrate oxalate, wash with 50 mL of deionized water, dry in a 60 ℃ oven, and collect the transition metal dihydrate oxalate.
[0038] The concentrations of lithium ions and corresponding transition metal ions in the supernatant of Examples 1-3 and Comparative Example 1 are measured using an inductively coupled plasma optical emission spectrometer (ICP-OES), and the leaching rate, recovery rate, and Li + and Ni 2+ , Co 2+ , Mn 2+The separation selectivity of lithium ions and transition metal ions. The relevant parameters of Examples 1-3 and Comparative Example 1 and the leaching rate, recovery rate and separation selectivity calculation results are shown in Table 1.
[0039] Table 1: Test parameters and leaching rate, recovery rate and separation selectivity
[0040] Table 1: Comparative Example 1 and Comparative Example 1, the reaction time is shortened from 120 min to 20 min at the same temperature; and the Li / TMs selectivity in Example 1 is higher. Example 2 and Comparative Example 1 are compared, in the same reaction time, a larger solid-liquid ratio is treated at a lower reaction temperature, and the Li / TMs selectivity in Example 2 is higher. Example 3 and Comparative Example 1 are compared, and the reaction time is shortened from 120 min to 60 min at a lower reaction temperature. By comparison, the method of the present application couples the processes of dissolving and separating precipitation of fine powder in series, and completes the high-selectivity separation and recovery of lithium ions and transition metal ions in one pot.
[0041] Table 2: Comparison of reagent concentrations
[0042] As can be seen from Table 2, Examples 1-3 can complete the two reaction processes of dissolution-precipitation (S3) in one pot, the concentration ratio of oxalic acid dihydrate to fine powder is in the range of 0.9-1.1, and the ratio of oxalic acid dihydrate to reducing agent and in-situ acid releasing agent is in the range of 0.8-1.2. Comparative Example 1 requires two process steps of dissolution (S3) and precipitation (S4). The concentration of sulfuric acid required for dissolution is 4.0, and the concentration of sodium hydroxide required for precipitation is high. The reagent consumption is large, and the process steps are complicated.
[0043] The pH values of the reaction solutions of the dissolution-conversion processes (i.e. step S3 reaction process) of Examples 1-3 and the dissolution process (i.e. step S3 reaction process) of Comparative Example 1 were tested using a pH meter, as shown in Figure 1 It can be seen that the reaction of the examples is in a mild acid-base condition throughout, while the reaction of the comparative example is strongly acidic.
[0044] The Li + The leaching rate-time curves are shown in Figure 2 As shown in Figure 2As shown, the Li leaching rate in Example 1 reached a maximum of 98.9% in just 20 minutes, Example 2 reached a maximum of 99.0% in 120 minutes, and Example 3 reached a maximum of 98.8% in 60 minutes. The comparative example required 120 minutes to reach a maximum of 98.3%. Examples 1-3 achieved superior treatment results to Comparative Example 1, while being more energy-efficient, gentler, and requiring fewer process steps.
[0045] The XRD test patterns of NCM powder (prepared in step S1 of Example 1), LCO powder (prepared in step S1 of Example 2), and the recovered transition metal dihydrate oxalate obtained in Examples 1 to 3 and Comparative Example 1 were obtained respectively. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that after the refined powder materials in Examples 1 to 3 are converted into the corresponding transition metal dihydrate oxalate hydrates, the XRD peaks are clear and sharp, and there are no impurity peaks, indicating that the final obtained dihydrate oxalate hydrates have high purity and good crystallinity.
[0046] The comparison shows that the method of the present invention has the advantages of mild conditions, fast reaction rate, simplified process steps and high reagent utilization rate.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for recycling high-selectivity decommissioned lithium electric layered-oxide cathode concentrate, characterized by, The method comprises the following steps: S1. After pretreatment of the retired lithium battery layered oxide positive electrode sheet, a fine powder material is obtained; S2. Dissolve bivalent oxalic acid, a reducing agent and a coordination type in-situ acid releasing agent in deionized water in proportion to obtain an aqueous treatment solution; S3. Add the fine powder material to the aqueous treatment solution, heat and stir until the reaction is completed, and then stand to obtain a solid mixture; S4. After solid-liquid separation of the solid mixture, add sodium carbonate to the liquid substance to precipitate a solid lithium carbonate material, and collect the solid substance after washing and drying to obtain the recovered positive electrode material.
2. The method of claim 1, wherein the high selectivity de-commissioned lithium battery layered oxide cathode fine powder recovery method is characterized by, The pretreatment in S1 is: the retired lithium battery layered oxide positive electrode sheet is sequentially subjected to high-temperature calcination, impurity removal and grinding treatment to obtain a fine powder material, and the content of layered oxide in the fine powder material is more than 99%.
3. The method of claim 2, wherein the high selectivity de-commissioned lithium electric layered oxide cathode concentrate recovery process is characterized by, The layered oxide is one or a combination of lithium cobalt oxide (LiCoO2), nickel cobalt manganese ternary oxide (LiNi x Co y Mn 1-x-y O2), or nickel cobalt aluminum ternary oxide (LiNi x Co y Al 1-x-y O2).
4. The method of claim 1, wherein the high selectivity de-commissioned lithium battery layered oxide cathode fine powder recovery method is characterized by, In S2, the reducing agent is one or a combination of several of sodium sulfite, sodium bisulfite, potassium sulfite, potassium bisulfite and hydrogen peroxide; The coordination type in-situ acid releasing agent is one or a combination of several of malic acid, gluconic acid, ascorbic acid, tartaric acid, citric acid, succinic acid and tannic acid.
5. The method of claim 1, wherein the high selectivity de-commissioned lithium electric layered oxide cathode slurry powder recovery method is characterized by, In S2, in the aqueous treatment solution, the concentration of bivalent oxalic acid, the reducing agent and the coordination type in-situ acid releasing agent is 0.1-1.0 mol / L; And the molar ratio of bivalent oxalic acid: reducing agent: coordination type in-situ acid releasing agent is 1.0: 0.8-1.2: 0.8-1.
2.
6. The method of claim 1, wherein the high selectivity de-commissioned lithium electric layered oxide cathode slurry powder recovery method is characterized by, In S3, the solid-liquid ratio of the fine powder material to the treatment solution is 9.65-96.5 g / L; And the molar ratio of the fine powder material: bivalent oxalic acid is 0.9-1.1:
1.
7. The method of recovering high selectivity decommissioned lithium electric layered oxide cathode concentrate fines of claim 1, wherein, In S3, the heating temperature is 50-100 ℃, the reaction time is 10 min-2 h, and the standing time is 1-4 h.
8. The method of claim 1, wherein the high selectivity de-commissioned lithium battery layered oxide cathode slurry powder recovery method is characterized by, In S4, the concentration of lithium ions in the liquid substance is 2.0-8.0 g / L, and the pH value is 6.5-7.
5.
9. Use of the recovery method according to any one of claims 1-8 in recycling a retired sodium battery layered oxide positive electrode fine powder.
10. A sodium-ion battery, characterized in that, The positive electrode material of a sodium ion battery is the positive electrode material obtained by the recovery method according to any one of claims 1-8.